Evaluation of Teacher Working Group Program (KKG) of Islamic religious education in Masohi Maluku Tengah - St Jumaeda; Nursaid Nursaid; Saddam Husein (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
The enhancement of professional skills of Islamic religious education teachers can be done with a professional coaching system through the KKG, as a platform to anticipate various problems that teachers encountered in conducting learning activities in the classroom, In addition, teachers can exchange thoughts, raise problems together in the KKG, solve and find the best way together and assisted by the facilitator and teacher of the subjects. The research aims to determine the level of achievement of KKG of Islamic religious education at elementary school level, in Masohi regency of Maluku Tengah. The study uses evaluative research methods on KKG activities of the PAI subjects using a goal-oriented evaluation model developed by Ralph Winfred Tyler. Where the focus is on research into the level of goal achievement. The collection of data conducted in the evaluation study of KKG's activity program of PAI's subjects in Masohi, was conducted using observation techniques, interviews, questionnaires, and documentation. The subjects in this study were principals, PAI teachers, and the KKG-PAI manager of Masohi. The results showed that the result of input evaluation related to KKG capacity includes activity activities KKG PAI has an average score, 84.21%, management performance KKG PAI has an average score of 90.07%, facilities and infrastructure KKG has a score an average of 82.91%, KTSP availability in school member KKG has a score of 93.65%. The implementation of learning has an average score of 87.36%, and the learning results assessment has an average score of 84.13%. Overall evaluation of inputs related to the capacity of KKG PAI Masohi is in good category. Meanwhile, for aspects of the output related to the competency of teachers in the school, members of the KKG, have a 91.2% of the average value of the teacher's competence